The relationship between self-reported chronic stress, physiological stress axis dysregulation and medically-unexplained symptoms - Schulz, André; Larra, Mauro F.; Vögele, Claus; Kölsch, Monika; Schächinger, Hartmut (Biological psychology, 2023)
The positive feedback model of medically-unexplained symptoms posits that chronic stress affects the activity of the physiological stress axes, which in turn generates medically-unexplained symptoms. As a first step to empirically test its model assumptions, we investigated potential associations between chronic stress, physiological stress axis activity and medically-unexplained in a cross-sectional study. One hundred-ninety-nine healthy individuals provided self-reports on chronic stress and medically-unexplained symptoms, resting heart rate/variability (HR/HRV; e.g., root mean square of successive differences/RMSSD, low frequency/LF power), cortisol awakening response (CAR) and diurnal cortisol. Significant positive contributors to medically-unexplained symptoms were the chronic stress scales ‘lack of social appreciation’ and ‘chronic worries’, as well as CAR and LF HRV; diurnal cortisol was a negative contributor. Mediation analyses showed that the impact of neural indicators associated with physiological stress axis activity (HR/HRV) related to medically-unexplained symptoms, which was mediated by chronic stress, whereas the mediation effect as suggested by the positive feedback model was not significant. These cross-sectional findings do not support the positive feedback model. Longitudinal studies are required to conclude about potential mechanistic and causal relationships in the model. Nevertheless, our mediation analyses give first indication that the constitution of physiological stress axes may play a major role in how stressors are perceived and which kind of health-consequences (e.g., medically-unexplained symptoms) this may have. •Chronic stress is a positive contributor to medically-unexplained symptoms (MUS).•Low frequency heart rate variability (HRV) is a positive contributor to MUS.•Cortisol awakening response is a positive contributor to MUS.•Chronic stress mediates the relationship between HRV and MUS.•Physiological stress axes may play a major role in how stressors are perceived.